2019
DOI: 10.1177/0733464819831596
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning and Advance Directives: A Multimedia Education Program in Community-Dwelling Older Adults

Abstract: This community-based cluster randomized trial evaluated the efficacy of a 4-week multimedia educational intervention followed by telephone consultations at Weeks 12 and 24 on the selection of a hospice program for end-of-life care and completion of an advance directive (AD) in case of future advanced dementia. One hundred twenty-three cognitively intact older adults from five community centers in Taiwan were randomly assigned to two groups. The study showed that 100% of participants in the interventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Interactive, multimedia/multimodal online programs included videos, interactive values questions, and/or written materials, such as ADs, booklets, pamphlets, or workbooks 101‐105 . Three programs were designed for low‐literacy populations 102,106,107 and two for non–English‐speaking participants 23,108 . One study included patient and surrogate interventions, 103 and one included patient and clinician interventions 89,109 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interactive, multimedia/multimodal online programs included videos, interactive values questions, and/or written materials, such as ADs, booklets, pamphlets, or workbooks 101‐105 . Three programs were designed for low‐literacy populations 102,106,107 and two for non–English‐speaking participants 23,108 . One study included patient and surrogate interventions, 103 and one included patient and clinician interventions 89,109 …”
Section: Resultsmentioning
confidence: 99%
“…[101][102][103][104][105] Three programs were designed for lowliteracy populations 102,106,107 and two for non-Englishspeaking participants. 23,108 One study included patient and surrogate interventions, 103 and one included patient and clinician interventions. 89,109 Some written-only interventions included questions about values (i.e., not ADs) designed to initiate conversations with clinicians [110][111][112][113] or included in nursing home records.…”
Section: Intervention Modalitiesmentioning
confidence: 99%
“…This suggests that developing ADs is closely related to people’s intention to control their own care and the right to refuse futile treatments [ 30 ]. Existing studies have reported that educational interventions are effective in assisting ACP implementation and AD completion among older adults [ 32 , 33 ]. Among the participants in our study, those who had received an educational program regarding EOL issues at various institutions, including welfare and nonprofit organizations, were also more likely to have ADs.…”
Section: Discussionmentioning
confidence: 99%
“…Documentation of ACP/AD: 54 RCTs evaluated documentation of ACP or AD 24 29–31 35 40–43 59 61 64 68 71 74 81 82 86 91 101 110–112 118–148. Of the 34 (63%) showing a positive and significant effect of the intervention on documentation, 20 were high-quality, 24 (71%) were communication interventions24 30 31 35 41 42 59 64 68 91 101 111 112 118–128 including 1 with a decision aid component,118 8 were decision aids only82 86 129–134 and 2 were AD-only interventions 43 135…”
Section: Resultsmentioning
confidence: 99%